Mycoflora associated with two species of Liliaceae in Bangladesh - Shamsi, Shamim; Naher, Najmun (Dhaka University Journal of Biological Sciences, 2013)
A total of nine fungi were isolated from two ornamental angiosperms, namely Hemerocallis fulva L. and Pancratium verecundum Ant. belong to Liliaceae. Three species of fungi were found to be associated with the leaf of Hemerocallis fulva. The fungi were Colletotrichum capsici, (Syd.) Bull. & Bisby, Colletotrichum dematium (Pers. Ex Fr.) and Glomerella montana (Sacc.)v Arx & E. Muller. Six species of fungi, namely Alternaria alternata (Fries) Keissler, Colletotrichum orbiculare (Berk & Mont.) Arex., Curvularia clavata Jain, Fusarium solani (Mort.) Sacc., Lasiodiplodia theobromae (Pat.) Griffon and Maubol and Macrophomina phaseolina (Tassi) Goid were found to be associated with P. verecundum. Among the fungal species Glomerella montana is new record for Bangladesh. Dhaka Univ. J. Biol. Sci. 22(1): 39-46, 2013 (January)